Characteristics of Nutritional Value in Making Mocaf Flour on Long Fermentation - Achmad, Fadhilah; Astuti, Suhartin Dewi; Astuti, Juni; Hambur, Kresensius (Program Studi Teknologi Pangan, 2024)
One of the prospective commodities to be developed as a food diversification material is cassava. Modified cassava flour or MOCAF (Modified Cassava Flour) is a modified starch product that has been widely used in various food products. Fermented cassava flour has advantages over ordinary cassava flour, namely high protein content and lower HCN. This study aims to determine the characteristics of nutritional value in making mocaf flour based on different fermentation times. This study used the Completely Randomized Design (CRD) method using a cassava dose of 500g and 0.5g of tape yeast consisting of 3 treatments, namely L1 (2 days), L2 (3 days), and L3 (4 days). The results showed that the analysis of nutritional value characteristics at the best treatment water content was treatment L1 (10.24%), nutritional value at the best carbohydrate and total titrated acid levels was treatment L3 (65.32% and 9.85%). The longer the fermentation, the higher the carbohydrate and total titrated acid content, but the lower the water content value.